Functionalized Silicon Electrodes Toward Electrostatic Catalysis - Zhang, Long; Yang, Xiaohua; Li, Shun; Zhang, JianMing (Frontiers in Chemistry, 2021)
Oriented external electric fields are now starting to emerge as “smart effectors” of chemical changes. The key challenges for experimentally studying electrostatic catalysis are (i) how to control the orientation of fields along the reaction axis and (ii) how to finely adjust the magnitudes of electrostatic stimuli. Surface models provide a versatile platform for addressing the direction of electric fields with respect to reactants as well as balance the trade-off between solubility of charged species and intensity of electric fields. In this mini review, we present the recent advances that have investigated the electrostatic effect on the chemical reaction on the monolayer-functionalized silicon surfaces. We mainly focus on elucidating the mediator/catalysis role of static electric fields induced from either electric double layers solid/liquid at electrode/electrolyte interfaces or space-charge in the semiconductors, indicating the electrostatic aspects is of great significance on the semiconductor electrochemistry, redox electroactivity and chemical bonding. Herein, functionalization of silicon surfaces allows scientists to explore electrostatic catalysis from nanoscale to mesoscale, most importantly, it provides glimpses of the wide-ranging potential of oriented electric fields for switching on/off macroscale synthetic organic electrochemistry and living radical polymerization.